Istanbul fast food trends by analyzing variables resulting in customer satisfaction - Amin, Aysha Binte (My University, 2021)
Bu araştırmanın amacı, fast food endüstrisinde müşteri memnuniyetine yön veren trendleri farklı faktörlerüzerinden değerlendirmektir. Fast food sektöründe müşteri memnuniyetine yol açan analizlerde yemekkalitesi, hizmet kalitesi, ambiyans ve fiyatlandırma, COVID-19 gibi çeşitli bağımsız değişkenler dikkatealınır ve fast food trendlerini de gösterir. Araştırma ayrıca pandemi sırasında fast food müşterilerinin satınalma eğilimlerini gözlemlemeye odaklanmıştır. Araştırma İstanbul merkezlidir. Demografi, cinsiyet, gelir,yaş ve istihdam durumunu içerir. Tüketici zevklerindeki sayısız değişikliğe ve toparlanan bir ekonomiyerağmen, son beş yılda küresel gıda endüstrisi hala büyümeyi başardı. Tüketiciler, harcanabilirgelirlerindeki artışla birlikte dışarıda yemek yeme harcamalarını nispeten artırdı. Fast food işletmeleribunun sonucunda tüketicilere tam zamanlı restoran hizmetleri sunmaya başladı. Dünya çapında fast foodrestoranlarının pazar büyüklüğü 885.1 milyar dolardır ve pazar büyüklüğü 2021'de %2.1'dir (Küresel FastFood Restoranları - Pazar Büyüklüğü 2003–2026, 2020). Araştırmada betimsel analiz ve girişimsel analizkullanılmıştır. Dört bağımsız değişkenin anlamlılığının ortaya konduğu araştırma sonuçları için regresyonanalizi uygulanmıştır. Sonuçlar, gıda fiyatlarının ve kalitesinin müşteri memnuniyeti üzerinde önemli biretkiye sahip olduğunu göstermiştir. Shake Shack ve Arby's, ankete katılanlar tarafından en sık ziyaretedilen fast food restoranları olarak seçildi. Ayrıca sonuçlar, pandemi (COVID-19) başlangıcından bu yanafast food satın alımlarında bir artış olduğunu gösterdi.

The purpose of this research is to evaluate customer satisfaction leading trends in the fast-food industrythrough different factors. Various independent variables such as Quality of food, Quality of Service,Ambiance, and Pricing, COVID-19, are taken in account for analysis leading to customer satisfaction inthe fast food industry and displaying the fast food trends. The research has also focused on observing thepurchasing trends of customers of fast food during the pandemic. The research is Istanbul centric.Demographics include gender, income, age, and employment status. Despite the numerous changes inconsumer taste and an economy that is recovering, over the past five years, the global food industry hasstill been able to grow. Consumers relatively increased spending on dining out with the increase in theirdisposable income. Fast food businesses, as a result, started providing full-time restaurant services to theconsumers. The market size of fast-food restaurants globally is $885.1 billion, with the market sizegrowth of 2.1% in 2021 (Global Fast Food Restaurants - Market Size 2003–2026, 2020). Descriptiveanalysis and interferential analysis have been used in the research. Regression analysis has been appliedfor research results through which significance of the four independent variables has been revealed. Theresults have displayed that price and quality of food have a significant effect on customer satisfaction.Shake Shack and Arby’s have been chosen as the most frequently visited fast food restaurants by therespondents. Furthermore, the results exhibit an increase in fast food purchasing ever since the start of thepandemic, COVID-19.
Keywords: Business; Covid-19; Covid-19 Customer Satisfaction; Customer Satisfaction; Fast Food; İşletme